Deploying the production plan for winter-spring season 2019-2020 in the Mekong River Delta (MRD) region - Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A directive from the Department of Crop Production instructing local authorities of provinces in MRD to implement the winter-spring production plan (including the planting calendar adjustment based on CS-MAP).